Blind oracles : intellectuals and war from Kennan to Kissinger - Kuklick, Bruce, 1941- (Princeton paperbacks, 2007)
In this trenchant analysis, historian Bruce Kuklick examines the role of intellectuals in foreign policymaking. He recounts the history of the development of ideas about strategy and foreign policy during a critical period in American history: the era of the nuclear standoff between the United States and the Soviet Union. The book looks at how the country's foremost thinkers advanced their ideas during this time of United States expansionism, a period that culminated in the Vietnam War and détente with the Soviets. Beginning with George Kennan after World War II, and concluding with.